2006
DOI: 10.1097/01.ogx.0000238646.91712.3e
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Age Has Differential Effects on DNA Damage, Chromatin Integrity, Gene Mutations, and Aneuploidies in Sperm

Abstract: Numerous trials have concluded that laparoscopic hysterectomy, compared with total abdominal hysterectomy, causes less postoperative pain and shortens the hospital stay. Many view this approach as being more cost-effective, but a recent large, randomized trial demonstrated more major complications after the laparoscopic procedure. The present study compared the length of time in the hospital, time to convalescence, and long-term patient satisfaction in 47 consecutive women who were to have supravaginal hystere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 24 publications
5
47
0
3
Order By: Relevance
“…In the present study, no correlation was found between the age of our patients and the levels of DNA fragmentation. This is in agreement with the results of Dakouane et al [38] who found no difference in DNA fragmentation rate according to age among 212 men aged between 25 and 70 years, but in disagreement with the results of others studies [39,40] who had found a significant correlation between DNA fragmentation and age of the patients. In addition, a positive correlation was found between the rate of sperm DNA fragmentation and the rate of sperm chromosomal aberration.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, no correlation was found between the age of our patients and the levels of DNA fragmentation. This is in agreement with the results of Dakouane et al [38] who found no difference in DNA fragmentation rate according to age among 212 men aged between 25 and 70 years, but in disagreement with the results of others studies [39,40] who had found a significant correlation between DNA fragmentation and age of the patients. In addition, a positive correlation was found between the rate of sperm DNA fragmentation and the rate of sperm chromosomal aberration.…”
Section: Discussionsupporting
confidence: 87%
“…This is in agreement with the results of another study of the same population that used a sperm FISH assay specific for numerical chromosomal abnormalities, i.e., aneuploidy and diploidy (77). Previous results from other FISH studies provided ambiguous evidence for an association of men's age and autosomal aneuploidies in sperm (37,(77)(78)(79)(80)(81).…”
Section: Figuresupporting
confidence: 91%
“…Age of human subjects had been shown to have strong effect on sperm chromatin defects. Aged men had significantly higher DNA fragmentation index; the damage was found to be doubled between 20 and 60 years of age (Wyrobek et al, 2006). In our study apart from the 65 week age roosters the 23 week age roosters were also found to have higher DNA fragmentation.…”
Section: Discussionmentioning
confidence: 42%